The MCPC evolution in evolutionary computation - Esquivel, Susana Cecilia (1999)
The aItemative proposed and known as MCPC [6] has improved the perfonnance of the original Holland's Genetic Algorithms in order to obtain good quality solutions in less execution time. But, it's brought out an important concept in Evolutionary Computation:the relationship between exploration and exploitation of solutions in a problem space.